From the Measurement of Economic Performance and Social Progress to Well-being oriented Economic Policy - Feigl, Georg (Momentum Quarterly, 2017)
This article follows the initiatives to foster a societal and economic re-focussing on wellbeing and socialprogress, which appeared after the ground-breaking report of the “Commission on the Measurement of Economic Performance and Social Progress” led by Joseph Stiglitz. Departing from the Thesis that wellbeing-orientation is adequate for economic policy making but will not be successful on its one; it is argued that a better measurement of wellbeing and social progress together with a discursively and institutionally anchoring of wellbeing-orientation within the economic governance are needed. A Magic Polygon for wellbeing-oriented economic policy is proposed to link the new paradigm with the wellbeing-indicators. Within a general framework of commonly shared objectives of economic policy, current priorities would become negotiable. This contribution sketches an operational proposal for Austria and presents ideas for a stronger institutional and discursive anchoring of wellbeing-orientation within the economic governance. Finally four entry projects are given as an example of policies which should be undertaken given the current situation within a stronger wellbeing-orientated economic governance.
Keywords: Well-being; economic policy; economic governance; prosperity; magic polygon